MOBILITAS KOMUNITAS PESANTREN DI RANAH SOSIAL POLITIK - Nur Ahmad Fadhil Lubis (Badan Litbang dan Diklat Kementerian Agama RI, 2009)
Islamic boarding school is an educational institution which is unique and also dynamics. Unique, since Islamic boarding school is still able to survive among a rapidly changing environment. Islamic boarding school’s response towards such changes is made through adaptation, accommodation and adoption in a smart and wise manner. Islamic boarding school does not lose its-own identity as a tfaqquh fiddin institution. This paper attempts to make a critical review on various studies and papers on Islamic boarding school in relation to social mobility. Review is also conducted on the level of concept which underlies the discourse and theoretical frame above which it is built various explanations and conclusions on Islamic boarding school phenomenon, especilally those related to its mobility in social political arena